SECURITIZATION OF NETANYAHU’S RHETORIC POST 7 OCTOBER 2023 ATTACKS - Hikmatullah Idrus, Muh Rizky; Purnama, Chandra; Hermawan, Yulius Purwadi (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2025)
This article aims to analyze how Netanyahu's securitization construction after the Hamas attack on October 7, 2023 in Israel, by using securitization theory and theory of speech act. The results show that the securitization focused by Netanyahu’s speech act which carried out by three stages; the identification stage can be observed on how Netanyahu in his statements and actions towards Hamas after 7 October 2023; The emergency action can be observed on how Israel responds to it by devastating bombardment of Gaza; Impact on inter-unit relations can be observed on how Hamas responded to Israel's counterattack after its attack on 7 October 2023. In the constellation that occurred, there were several actors involved, namely Israel-IDF, Hamas, and Hezbollah. Moreover, non securitization observed on conditions before 7 October 2023, where Israel focused only on its own internal problems. Politicized observed on how Netanyahu by his speech to his audience (Israeli citizens) who suggested them that they were in a 'war' situation with Hamas. Securitized observed on how Netanyahu along with his staff Defense Secretary Yoav Gallant and Secretary Benny Gantz in his press conference rejected growing international criticism over the civilian cost of the war, and urged Western leaders to lend their support to them because victory would mean victory for the rest of the world